Path of Nascent Polypeptide in Exit Tunnel Revealed by Molecular Dynamics Simulation of Ribosome - Ishida, Hisashi (The Biophysical Society, 2008)
Molecular dynamics simulations were carried out on Thermus thermophilus 70S ribosome with and without a nascent polypeptide inside the exit tunnel. Modeling of the polypeptide in the tunnel revealed two possible paths: one over Arg(92) of L22 and one under (from the viewpoint of 50S on top of 30S). A strong interaction between L4 and Arg(92) was observed without the polypeptide and when it passed over Arg(92). However, when the polypeptide passed under, Arg(92) repositioned to interact with Ade(2059) of 23S rRNA. Using steered molecular dynamics the polypeptide could be pulled through the L4-L22 constriction when situated under Arg(92), but did not move when over. These results suggest that the tunnel is closed by the Arg(92)-L4 interaction before elongation of the polypeptide and the tunnel leads the entering polypeptide from the peptidyl transferase center to the passage under Arg(92), causing Arg(92) to switch to an open position. It is possible, therefore, that Arg(92) plays the role of a gate, opening and closing the tunnel at L4-L22. There is some disagreement over whether the tunnel is dynamic or rigid. At least within the timescale of our simulations conformational analysis showed that global motions mainly involve relative movement of the 50S and 30S subunits and seem not to affect the conformation of the tunnel.